(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The inhibition effect of eugenol oil (EO) on the corrosion of tin in 0.1 M Na2CO3 has been studied by electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization technics. The effect of temperature on the corrosion behavior of tin in 0.1 M Na2CO3 with and without addition of eugenol oil was studied in the temperature range 278-308 K. This compound inhibits the corrosion of tin at low concentration. At 4g/L eugenol oil the inhibition efficiency calculated by potentiodynamic polarization and EIS techniques is 70% and 82%, respectively. The inhibition efficiency increased with increase of the inhibitor concentration and decreased with increase of medium temperature. Electrochemical impedance spectroscopy was used to investigate the mechanism of corrosion inhibition. Polarization curves reveal that EO acts as a mixed-type inhibitor in corrosive solution. The results obtained from the different corrosion evaluation techniques are in good agreement.